The Marriage Innovation Practices of the Bangsamoro: The Maguindanao Cases - Abdulmaula U. Mantawil (RIRAI Publisher, 2022)
This study aimed to determine the Marriage Innovative Practices of the Maguindanaon in the Municipality of Datu Piang, Province of Maguindanao. The study focused on the Personal Profile of the respondents in terms of age, Sex, Civil Status, Educational Attainment both Secular and Islamic Education, the essential requisite in Muslim marriage in terms of Age, Offer (Ijab) and Acceptance (Qabul), Solemnization and Dowry, the Innovative marriage practices of the Maguindanaon in the Municipality of Datu Piang Province of Maguindanao in terms of Marriage Negotiation, Preparation for the Wedding Ceremony, Wedding Ceremony and Entertainment, the problems encountered in the innovation of marriage practices vis-à-vis marriage in Islam, the practices on marriage system can be drawn from this study that is acceptable to the Maguindanao culture and Islam. The study utilized the descriptive design and qualitative approach in the interpretation of the data. Through this method, the respondents were able to describe the innovative marriage practices of the Maguindanaon in Datu Piang, Maguindanao. The findings of the study revealed that Sixty five (65%) of respondents are male, while the remaining thirty five (35%) were female. All of them are residence of the Municipality of Datu Piang, Maguindanao. The age bracket 30 – 39 and 40 – 49 were the same frequency rated 30%. This was followed by age bracket 25 – 29 with a frequency of 20% followed by age brackets 50 – 59 with a frequency of 15%. While the age bracket 60 above were only 5% and nobody answered that they were below 25. Out of 100% respondents only 26% of the respondents were single while 75% of them were married. Only 20% of the respondents finished there tertiary education while the 60% of them finished their Kulliyyah in Islamic Education.